Implementasi Pendidikan Karakter Berbasis Pembiasaan dalam Meningkatkan Sopan Santun Peserta Didik Sekolah Dasar - Mira Yanti Lubis; Chairun Nisyah; Diana Safutri Hasibuan; Enni Royani Nasution; Indriani; Khoiria Hasibuan; Muhammad Zanuar Harahap; Nirmala Putri Salsabila Harahap (KENDURI : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
Character education is an important part in shaping the personality of students, especially at the elementary school level. One character that needs to be developed from an early age is politeness, which is reflected in students’ ability to respect teachers and friends, use good language, greet, ask permission, say thank you, apologize, and obey school rules. However, in practice, the habituation of polite behavior does not always occur consistently in students’ lives. This study aims to implement habituation-based character education as an effort to improve polite behavior among elementary school students in Handio Village, Padang Lawas Regency. The study used an action approach implemented through the stages of planning, implementation, observation, and reflection. The subjects were elementary school students in Handio Village. The program was implemented through activities to habituate greetings, smiling, greetings, using polite language, asking permission, saying thank you, apologizing, respecting teachers and friends, and obeying school rules. Data were collected through observation, questionnaires, interviews, and documentation. Data analysis was carried out descriptively quantitatively and qualitatively by comparing the conditions of student behavior before and after the program implementation. The results of this study are expected to show an increase in students’ polite behavior after participating in habit-based character education. This program is also expected to build a positive school culture and provide a simple, contextual, and sustainable character habit model for elementary schools in rural areas. This program is also expected to build a positive school culture and provide a simple, contextual, and sustainable character habit model for elementary schools in rural areas. This study has implications that character education will be more effective if it is not only delivered in the form of material, but is realized through role models, direct practice, positive reinforcement, and consistent habituation.